2021
DOI: 10.3390/plants10081734
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Digestate Use for Fertilization in an Agricultural Cropping System

Abstract: The need to find and maximize the use of alternative sources of nutrients for plants and soil environment have been on the forefront of research in sustainable agriculture. These alternatives have to be affordable, accessible, reproduceable, and efficient to compete with established inorganic fertilizers while at the same time reduce any potential negative impacts on the environment. We aimed to evaluate the effectiveness of digestate fertilization in an agricultural system over a period of three years. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 39 publications
(62 reference statements)
1
21
0
2
Order By: Relevance
“…Wheat straw is usually chopped and spread on the soil as a fertilizer to maintain the amount of humus present in the soil (Arlauskienė et al., 2009). Using the biomass yield of spring wheat straw in a related study under similar climatic conditions (Lithuania) (Doyeni et al., 2021), yield of spring wheat straw was 1.79 ± 0.06 Mg ha −1 . The data is not presented in the table as we took wheat straw as reference crop.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat straw is usually chopped and spread on the soil as a fertilizer to maintain the amount of humus present in the soil (Arlauskienė et al., 2009). Using the biomass yield of spring wheat straw in a related study under similar climatic conditions (Lithuania) (Doyeni et al., 2021), yield of spring wheat straw was 1.79 ± 0.06 Mg ha −1 . The data is not presented in the table as we took wheat straw as reference crop.…”
Section: Resultsmentioning
confidence: 99%
“…The highest average fresh and dry AGB value was achieved in BB digestate-treated variant despite the lowest value of TN and the third highest C ox content in soil. It was reported that digestates have a higher potential over a short- to mid-term use period to positively affect plant biomass yield in comparison to synthetic nitrogen fertilizer under favorable climatic conditions ( Doyeni et al., 2021 ). However, we discovered that plant nitrogen content (%) in plant dry biomass did not correspond to the amount of nitrogen amended with the respective digestate doses to the experimental variants.…”
Section: Discussionmentioning
confidence: 99%
“…Agriculture sector remains a focal point and has been included in the EU's overall policy framework to integrate crop and livestock management with different interfaces such as food production, environmental safety, waste utilization, energy generation from food and non-food crops, soil, and GHG reduction obligations. This realistic target has led to an intense drive in sustainably managing the nitrogen (N) flow in livestock farming, food production, organic and inorganic inputs to improve crop yield, productivity and with lesser effect on the soil and the environment (Doyeni et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%